2021
DOI: 10.3390/jcm10173782
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID: Distinction between Organ Damage and Deconditioning

Abstract: (1) Background: Long COVID syndrome refers to long-term sequelae of the novel viral disease, which occur even in patients with initially mild disease courses. However, there is still little evidence of the actual organic consequences and their frequency, and there is no standardized workup to diagnose long COVID syndrome yet. In this study, we aim to determine the efficiency of a stepwise diagnostic approach for reconvalescent COVID-19 patients with cardiopulmonary symptoms. (2) Methods: The diagnostic workup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
1
29
0
2
Order By: Relevance
“…All patients were included independently of their initial disease severity (ranging from asymptomatic to hospitalised courses). As recently published, diagnostic workups followed a strict examination algorithm 11 . In brief, all patients underwent transthoracic echocardiography, body plethysmography, capillary blood gas analysis (BGA) and a 6-min walk test (6-MWT).…”
Section: Methodsmentioning
confidence: 99%
“…All patients were included independently of their initial disease severity (ranging from asymptomatic to hospitalised courses). As recently published, diagnostic workups followed a strict examination algorithm 11 . In brief, all patients underwent transthoracic echocardiography, body plethysmography, capillary blood gas analysis (BGA) and a 6-min walk test (6-MWT).…”
Section: Methodsmentioning
confidence: 99%
“…30,33 Five studies reported chronotropic incompetence to be a major cause of reduced exercise capacity, 25,30,44,63,64 and most studies reported a lower peak heart rate among individuals with reduced exercise capacity. One study each specifically reported pulmonary fibrosis, 65 pulmonary vascular limitation, 66 impaired microcirculation, 61 endothelial dysfunction, 67 dysautonomia, 64 and loss of mechanical efficiency 28 as the primary etiology of reduced exercise capacity. Despite concerns about pulmonary thromboembolism during acute infection, pulmonary vascular limitations were uncommon.…”
Section: Resultsmentioning
confidence: 99%
“…These symptoms are often unspecific and manifest in various organ systems [ 27 ], which makes it difficult to prove causality between prior SARS-CoV-2 infection and patients' complaints. According to a follow-up study carried out by the University of Ulm, there is a discrepancy between functional complaints and barely measurable organ damage in post-COVID-19 patients [ 28 ]. This resembles the contrast between poor self-evaluation and normal physical performance tests in the SARS-CoV-2-positive cohort at hand.…”
Section: Discussionmentioning
confidence: 99%